ROLE OF RAINFALL ON THE HiILSA FISHERY ALONG THE ORilSSA COAST - Pati, S; Pati, D K (Indian Journal of Fisheries, 2011)
A close correlation is observed between the total annual rainfall and therate of landing of hilsa with drift gillnets {r = 0.6). The years of heavy precipitationare characterised by an abundance of hilsa. The normal rainfall associated with thesouth-west monsoon is in better correlation with the hilsa catch (r = 0.6) than theresidual rains of the north-east monsoon (r = 0.16).